Marine Invertebrate Inventory at Ai Limung Beach, Teluk Saleh, Sumbawa, West Nusa Tenggara, Indonesia - Erlangga, Haqqy R.; Hikmahyanti, Hikmahyanti; Solihin, M. (Syiah Kuala University, 2025)
Saleh Bay, which is a semi-enclosed water body bordering the Flores Sea, is located in the northeast coastal region of Sumbawa Island, West Nusa Tenggara. This area has potential for the utilization of various natural resources such as fisheries, tourism, agriculture, and industry. Increased human activities and ongoing development around the coastal area of Teluk Saleh have put pressure on marine habitats, impacting ecosystem health and water quality. Invertebrate biota, as part of the kingdom Animalia, play an important role in ecosystems as environmental bioindicators and providers of significant ecological services. However, data on the presence and diversity of marine invertebrates in this area are still very limited. Therefore, this study was conducted at Ai Limung Beach, Pungkit Village, Sumbawa Regency, with the aim of identifying marine invertebrate species and evaluating their ecological and economic roles. The results of this study are expected to serve as a reference for stakeholders in managing marine resources in the Teluk Saleh area, supporting conservation efforts, and facilitating sustainable resource utilization policies.